Experimental study and numerical simulation of flow over the inclined airfoil-shaped weir in rectangular channel. (December 2022) - Sun, Bin; Song, Zhanqi; Yang, Lei; Li, Cheng; Li, Zhiwei
Abstract: In order to find an integrated flow measurement and control facility with stable outflow form, a series of experiments and numerical simulations were performed for the inclined airfoil-shaped weir. Based on the experimental and simulated data, the stage-discharge relationship was deduced by using dimensional analysis and incomplete self-similarity theory. And two flow measurement formulas with inclination angle of 0°–45° were obtained through different fitting schemes. The variation law of discharge ratio with inclination angle and the accuracy comparison of flow measurement formulas were analyzed. Moreover, the Froude number, critical submergence degree, head loss and velocity distribution of the flow field over the weir were studied. The results show that streamlined airfoil improves the stability of flow behind the weir. The average relative error of the free water surface line data between experiments and simulations is 5.05%, which indicates the reliability of the numerical simulation. The discharge ratio proposed in the fitting scheme I takes the 25° inclination angle as the limit, which increases slightly at first and then decreases gradually, and the flow measurement relative errors of the two fitting formulas are all within ±7%. The average Froude number of the upstream reference section at each inclination angle is less than 0.25, the critical submergence range is between 0.87 and 0.96, and the relative head loss ranges from 3.54% to 12.16%, so as to ensure the accuracy of flow measurement. Highlights: An integrated flow measurement and control facility with stable outflow form is proposed. The flow field of the inclined airfoil-shaped weir was simulated by RNG k-ε turbulence model. The flow measurement formula was deduced by dimensional analysis and the hydraulic performance were analyzed.